Gas nitriding and subsequent oxidation of Ti-6Al-4V alloys - Lee, Dong Bok (Springer, 2012)
Ti-6Al-4V alloys consisting of α-Ti grains and intergranular β-Ti islands were nitrided at 850°C for 1 to 12 h under a nitrogen pressure of 1 Pa. With increasing nitriding time, the Ti-N compound layer became thicker, and the α-Ti diffusion zone containing dissolved nitrogen became wider. In the Ti-N compound layer, the initially formed Ti(2)N became TiN as the nitriding progressed. The nitride layers were oxidized to rutile-TiO(2 )after oxidation at 700°C for 10 h in air.